Understanding the Thermal Cracking for Anthracene Molecule : A DFT Approach - Yousif, Qhatan A; Shanshal, Muthana A (Al-Nahrain Journal of Science, 2018)
Density Functional Theory (DFT) calculations were carried out to study the thermal cracking for anthracene molecule to estimate the bond energies for breaking the following bonds C1-C2, C1-C9a,C9-C9a, C2-C3, C1-H1,C2-H2,and C9-H9 as well as the activation energies. The activation energy values for C1-H1, C2-H2, and C9-H9 bond breakage is lower than required for C1-C2, C1-C9a, and C9-C9a. The carbon - hydrogen bond rupture depends only slightly on the position in the molecule so the values of reaction energy is close to 117 kCal/mol and unlike the carbon-carbon bonds. It seems that the characteristic planarity is important factor to acquire the molecule structure the required stability along the reaction paths. The trends in the bond energies and the configuration structures are discussed.